Management of erectile dysfunction: barriers faced by general practitioners - Low, W.Y.; Ng, C.J.; Tan, N.C.; Choo, W.Y.; Tan, H.M. (2004)
Aim: To explore the barriers faced by general practitioners (GPs) in the management of patients with erectile dysfunction (ED). Methods: This was a qualitative analysis of focus group discussions and in-depth interviews involving 28 Malaysian GPs. Results: GPs' perception of ED being not a serious condition was a major determinant of their prescribing practice. Doctor's age (younger), gender (female), short consultation time and lack of experience were cited as barriers. The GPs' prescribing habits were heavily influenced by the feedback from the first few patients under treatment, the uncertainty of etiology of ED without proper assessment and the profit margin with bulk purchase. Other barriers include Patients' coexisting medical conditions, older age, lower socio-economic status, unrealistic expectations and inappropriate use of the anti-impoteneet drugs. Cardiovascular side effects and cost were two most important drug barriers. Conclusion: The factors influencing the management of ED among the general practitioners were multiple and complex. An adequate understanding of how these factors (doctors, patients and drugs) interact can assist in the formulation and implementation of strategies that encourage GPs to identify and manage ED patients.